Rubbish and Recycling - Stephanie Turnbull (London, United Kingdom Usborne Publishing Ltd, 2007)
Usborne Beginners are colourful information books for children beginning to read on their own. Vivid, full colour illustrations and photographs on every page, accompanied by short, informative text.
Keywords: Sharing The Planet -- -Waste Management